GLOBAL RELATIONS BETWEEN SEISMIC FAULT PARAMETERS AND MOMENT MAGNITUDE OF EARTHQUAKES - Papazachos, B. C.; Scordilis, E. M.; Panagiotopoulos, D. G.; Papazachos, C. B.; Karakaisis, G. F. (Bulletin of the Geological Society of Greece, 2004)
The most reliable of the globally available relative data have been used to derive empirical formulas which relate the subsurface fault length, L, the fault area, S, and fault width, w, with the moment magnitude, M. Separate such formulas have been derived for earthquakes generated by strike-slip faulting, by dip-slip faulting in continental regions and by dip-slip faulting in lithospheric subduction regions. The formula which relates the fault area with the magnitude is combined with the definition formulas of seismic moment and moment magnitude to derive also relations between the fault slip, u, and the moment magnitude for each of the three seismotectonic regimes. For a certain magnitude, the fault length is larger for strike-slip faults than for dip-slip faults, while the fault width is small for strike-slip faults, larger for dip-slip faults in continental regions and much larger for dip-slip faults in regions of lithospheric subduction. For a certain magnitude, fault slip is about the same for strike-slip faults and dip-slip faults in continental regions and smaller for dip-slip faults in regions of lithospheric subduction.